Analysis of the of the Career System at Varo Tech Indonesia Limited Liability Company - Pratiwi, Ashfi; Darmastuti, Dhian; Haq, Ahmas Muhashisul (LPPM STIAB Jinarakkhita Lampung, 2024)
System career is something very important in development system employment at a company. Meanwhile, from the employee system, a career can become an encouraging thing and increase rank or position. The mobility system of a career at the company covers promotion, transfer, or demotion positions. The purpose of doing this study is to know if the system of career at Varo Tech Indonesia Limited Liability Company already walks in accordance with planning and if the company already supports the development of career employees. Research This nature is qualitative-descriptive, with an approach that is qualitative, through an interview and study process. References. Research result This discloses that the Career System at Varo Tech Indonesia Limited Liability Company has been implemented in the company and delivered to employees. Where is the system of careers at the company? This is not rigid, so the employees can make it easier. If there is a constraint or desire to move positions within the company, Besides opportunity employee for promoted open for all over employee. Mobility careers in this company are flexible so that every employee can keep going and develop their career. Result of the study It can be concluded that the planning system career has been implemented by Varo Tech Indonesia Limited Liability Company in the city of Tangerang, and as far as this has already been accomplished.